2011
DOI: 10.1126/science.1203080
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Rotational, Relaxational, and Shear Dynamics in Solid 4 He

Abstract: Using a high-sensitivity torsional oscillator (TO) technique, we mapped the rotational and relaxational dynamics of solid helium-4 ((4)He) throughout the parameter range of the proposed supersolidity. We found evidence that the same microscopic excitations controlling the torsional oscillator motions are generated independently by thermal and mechanical stimulation. Moreover, a measure for the relaxation times of these excitations diverges smoothly without any indication for a critical temperature or critical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
1

Year Published

2012
2012
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 34 publications
5
44
1
Order By: Relevance
“…On the other hand, we found that the thermal conductivity is insensitive to the amplitude of oscillations. As was noted earlier [25,26], the dependences of the TO resonant frequency on amplitude V look basically identical to the temperature dependences Fig. 5), our exponent γ ≈ 0.71 is substantially different.…”
Section: Torsion Oscillations Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…On the other hand, we found that the thermal conductivity is insensitive to the amplitude of oscillations. As was noted earlier [25,26], the dependences of the TO resonant frequency on amplitude V look basically identical to the temperature dependences Fig. 5), our exponent γ ≈ 0.71 is substantially different.…”
Section: Torsion Oscillations Resultssupporting
confidence: 60%
“…Softenning of solid helium caused by large-amplitude oscillations is then associated with stress-induced breakaway of 3 He impurities from dislocations. The related nonlinearities, hysteresis and long relaxation times [26] would indicate strong deviations from thermodynamic equilibrium, discussed in the next paragraph. The increase in the phonon mean free path upon either adding 3 He or annealing can be explained by reducing the number of dislocation segments capable of vibrating at frequencies of thermal phonons.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that the data are consistent with a picture of a thermal activation process of superfluid vortices through a nucleation barrier. This result is in contradiction with the interpretation of the experimental data of [13] where the self-similar v and T dependence of the superfluid fraction was understood to be proof of a coupling between elasticity and the NCRI. We also tried to find a self-similar relation, but there was less clear evidence of a correlation between the critical velocity and temperature than that provided by Eq.…”
Section: Prl 109 045301 (2012) P H Y S I C a L R E V I E W L E T T Econtrasting
confidence: 55%
“…Related to this, recent experimental results on supersolid helium have suggested a strong interplay between rotation and relaxation [13]. There, the supersolid fraction decreases with increasing temperature and rotation frequency in a specific way, even if in this case the role of the torsion rod is questioned [12,14].…”
mentioning
confidence: 98%
See 1 more Smart Citation